Zingiber Salarkhanii (Zingiberaceae), A new species from Bangladesh (Bangladesh Journal of Plant Taxonomy, 2013)
Zingiber salarkhanii Rahman et Yusuf, belonging to the family Zingiberaceae, is described and illustrated from Bangladesh as a new species. It was collected from six different localities of hilly forests in Chittagong, Khagrachari and Moulvi Bazar districts. Morphological diagnostic characters of closely related species of the genus are discussed.DOI: http://dx.doi.org/10.3329/bjpt.v20i2.17398Bangladesh J. Plant Taxon. 20(2): 239-242, 2013